Dispositional Resilience as Mediator in Psychological Stress on Healthcare Workers: A Multi-Group Analysis of Frontline and Non-Frontline Workers - Silvia Platania; Stefania Valeria Gruttadauria; Martina Morando (MDPI AG, 2022)
The experiences of healthcare workers (HCWs) during COVID-19 have been characterized by psychological symptoms such as stress, anxiety and depression, compassion fatigue and post-traumatic stress, which are long-lasting. The general picture of HCWs, especially frontline workers, is that of a physically and psychologically exhausted group. The aim of the study was to examine the potential mediating role of dispositional resilience in the impact of depression, anxiety and stress on professional quality of life among HCWs during the pandemic period. We also investigated possible differences between the frontline and non-frontline HCWs. The study enrolled 487 participants from public Italian hospitals. The variables of stress and anxiety predicted all factors related to professional quality of life, against depression which positively predicted only burnout and secondary traumatic Stress. Resilience was an important mediator in all these paths and the multigroup analysis suggested statistically significant differences between frontline and non-frontline HCWs. Results emphasised the importance of caring and concern for frontline HCWs to improve their quality of life, satisfaction and have positive impacts on the quality of service and care provided. There is a need to reflect on the necessity to develop projects and protocols that address health emergencies in advance.